Comparative value of visual and quantitative analysis of thallium-201 imaging after exercise in patients with an abnormal baseline repolarization on the electrocardiogram at rest - Niemeyer, M G; Ascoop, C A; Cramer, M J; Verzijlbergen, J F; Go, T L; van der Wall, E E; Zwinderman, A H; Pauwels, E K (European heart journal, 1990)
In this study the role of visual assessment and quantitative analysis of thallium-201 myocardial stress perfusion scintigraphy (MPS) was evaluated in patients with a normal electrocardiogram (ECG) (group I) and in patients with an abnormal baseline repolarization on the ECG (group II). One-hundred-and-thirty-five patients were studied. Group I consisted of 93 patients, 65 of whom had coronary artery disease (CAD), i.e. a luminal stenosis of greater than or equal to 50%; group II consisted of 42 patients, 32 of whom had CAD. In group II the exercise ECG was considered uninterpretable and thus only visual and quantitative analysis of MPS was investigated. Sensitivity and specificity of exercise electrocardiography, visual assessment and quantitative analysis of MPS were not significantly different in group I: sensitivities of the three methods were 66, 62 and 55% respectively, and specificities 86, 79 and 96% respectively. In group II there were no significant differences in the sensitivities and specificities of visual assessment or quantitative analysis of MPS: sensitivities of the two methods being both 88% and specificities both 80%. Visual assessment of redistribution (P less than 0.05) and quantitative analysis of washout (P less than 0.005) was significantly superior in group II than in group I; probably because of a higher incidence of three-vessel disease in the second group.